A Case Report of Phenytoin-Induced Anti-Neutrophil Cytoplasmic Antibody (ANCA) Associated Vasculitis - MD, Kyoung Sook Park; PhD,; Lee, Seungtaek; MD, Jeong Hae Kie; MD, Ea Wha Kang; PhD, (Archives of Clinical and Medical Case Reports, 2020)
Introduction: Phenytoin is a widely used anticonvulsant, but is rarely mentioned as one of the drugs responsible for atypical anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis. Therefore, we report a case of phenytoin-induced ANCA-associated vasculitis to arouse awareness. Case Report: A 65-year-old male patient was transferred to the emergency room with alteration of a semi-coma mental status and seizure due to intracerebral hemorrhage. Phenytoin (300 mg/day) was administered for the anti-epileptic effect but it was discontinued after one month of administration due to agranulocytosis. Approximately 50 days after hospitalization, the patient showed clinical features of acute glomerulonephritis, and results from ANCA testing (p-ANCA, anti-MPO antibody) were positive. Pathologic examination revealed suspicion of drug-induced ANCA-associated vasculitis. However, we could not determine any suspected drug at the time of pathologic diagnosis. The patient underwent hemodialysis, and high-dose steroid and IV cyclophosphamide therapy was administered to control vasculitis. Renal function was gradually recovered, and phenytoin was re-administered to treat status epilepticus. Following phenytoin retreatment, pancytopenia recurred and renal function deteriorated again. Due to the aggravation of renal dysfunction after re-administration of phenytoin and the pathologic suspicion of drug-induced ANCA-associated vasculitis, phenytoin was identified as the causative agent. Phenytoin therapy was stopped, and the renal function recovered with the disappearance of p-ANCA. The cyclophosphamide therapy was discontinued, and oral prednisolone dose was gradually tapered and discontinued after 2 months. Conclusions: We should be aware of phenytoin as a causative agent in drug-induced vasculitis to prevent severe organ damage and fatality.